Courseware design and learning: Pedagogical approach / Zarina Zainul Rashid and Mazliana Hasnan - Rashid, Zarina Zainul; Hasnan, Mazliana (2010)
With the rapid development of multimedia technology, multimedia educational courseware is widely available for educational purposes. Previous research showed that courseware can be an effective learning tool and motivate learning. In designing and developing courseware for teaching and learning purposes, it is very important that a developer should analyse and understand the pedagogical perspective. The main objective of this paper is to discuss courseware design from learning theories and pedagogy perspective. Based on the literature, constructive and behaviourism are believed to be the suitable learning theories incorporated in the design phase of Interactive Multimedia Computer Organization.